Incidence of affective factors in senior students’ oral production at Teodoro Gómez de la Torre High School, academic period 2022-2023 - Trujillo Aguirre, Dayana Nicole (2024)
Analyze the incidence of affective factors in the oral production of senior students at Teodoro Gómez de la Torre High School.